Studies on Outbreak of "New Duck Disease" in Kerala, India - Priya, P.M.; Pillai, Deepthi S.; Balusamy, C.; Rameshkumar, P.; Senthamilselvan, P. (International Journal of Poultry Science, 2008)
An outbreak of new duck disease with a mortality rate of 12.5 % was reported in Kerala, India. The causative agent, Reimerella anatipestifer was isolated and identified from all the dead birds.